BALANCED SCORECARD: ESSENCE AND IMPORTANCE FOR MAKING GOOD BUSINESS DECISIONS TO ENSURE SUSTAINABLE DEVELOPMENT OF BUSINESS - Pirogova T.E.,; Poluleh M.V.,; Golysheva N.I.,; Sorokina V.V.,; Martyinenko N.N., (Scientific Journal of Pedagogy and Economics, 2020)
In recent decades, the economic processes at both micro and macro levels have been affected significantly by the globalization, resulting in strengthening the ties and interaction between economies, promoting industrial development, tougher sector-wide competition and scientific and technological advancement. It has become increasingly challenging for many businesses to sustain a stable market position, not to mention business growth. It is beyond doubt that by focusing on growth and sustainability, economic entities develop the economy in general. However, it can affect other areas too. For example, expansion of production has a negative ecological impact, causing resource depletion and environmental pollution; and the desire to reduce costs often affects the working conditions and the wellbeing of employees. Recently, economic entities all over the world have been paying special attention to the environmental impact and social responsibility of business, which are two of the three main components of sustainable development. Therefore, the concept of sustainable development has been playing an increasingly significant role in every country in the world. Undoubtedly, many economic entities of today strive to adhere to the principles of sustainable development of business, which include economic success, environmental protection, and social wellbeing. The definition of “sustainable development” was first introduced in 1987 by the International Commission on Environment and Development. Despite this, the process of introducing the postulates of the International Commission into the activities of modern economic entities is still ongoing. Undoubtedly, many modern economic entities strive to adhere to the strategy of sustainable development, shaping their activities in the framework of compliance with the principles of financial success, causing the least damage to the environment and taking into account the social component. It is worth noting that the implementation of the concept of sustainable development in the management of a business entity requires the use of effective tools.